INNOVATIONS IN THE ICIREBON APP SERVICE AT THE CIREBON CITY LIBRARY AND ARCHIVES DEPARTMENT - Dea Liniawati; Iskandar Zulkarnaen (Yayasan Nuraini Ibrahim Mandiri, 2026)
Rapid technological advancements demand that public services become increasingly effective and efficient. One of the government’s efforts to leverage technology is through the implementation of e-government, which has spurred the emergence of public service innovations. In this context, the Cirebon City Library and Archives Office (Dispusip) developed the iCirebon application, driven by the commitment of the Cirebon City Government and Dispusip to enhance efficient public services and improve human resources through literacy. The objective of this study is to analyze the implementation of the iCirebon application service innovation at the Cirebon City Library and Archives Office using the theory of innovation success factors in the public sector, with indicators including governance and innovation, sources of ideas for innovation, innovation culture, capabilities and tools, objectives, outcomes, drivers, and barriers, as well as to collect data on the innovation itself. The research method used is qualitative, with data collection techniques including documentation, literature review, and in-depth interviews with key informants. The results of the discussion indicate that the iCirebon application innovation has been supported by regulations regading SPBE, Smart City policies and cooperation with third parties. Additionally, the innovation culture has been driven by visionary leadership. However, the actual innovation outcomes have not aligned with the initial objectives, as evidenced by the significantly low number of active application users. This stagnation is fundamentally caused by severe budget constraints, which have hindered system updates and rendered socialization efforts suboptimal.